2014
DOI: 10.1149/2.0511409jes
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium Cation Based Anion-Conducting Electrolyte Membranes Prepared by Radiation Induced Grafting for Direct Hydrazine Hydrate Fuel Cells

Abstract: Graft-type anion-conducting electrolyte membranes (AEMs) with imidazolium cations on graft polymers were synthesized through radiation-induced graft polymerization of N-vinylimidazole (NVIm) on poly(ethylene-co-tetrafluoroethylene) (ETFE) films, followed by N-propylation and ion-exchange reactions. The N-propylation proceeded quantitatively, whereas the ion-exchange reactions in 1 M KOH at 60 • C were accompanied by partial β-elimination of the imidazolium cations to yield copolymer grafts consisting of poly-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Since the ion‐exchange reaction from iodide to hydroxide in the grafted‐type AEM was very slow, requiring 48 h to ensure complete reaction, we conducted the ion‐exchange reaction in two steps: from An‐AEM/I to the chloride form, followed by transformation of the obtained chloride form to the hydroxide form to attain a high exchange degree, as shown in Scheme (b). First, the An‐AEM/I were transformed to the corresponding chloride form by soaking in 1 M HCl and 1,4‐dioxane at 60°C to facilitate the ion‐exchange reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the ion‐exchange reaction from iodide to hydroxide in the grafted‐type AEM was very slow, requiring 48 h to ensure complete reaction, we conducted the ion‐exchange reaction in two steps: from An‐AEM/I to the chloride form, followed by transformation of the obtained chloride form to the hydroxide form to attain a high exchange degree, as shown in Scheme (b). First, the An‐AEM/I were transformed to the corresponding chloride form by soaking in 1 M HCl and 1,4‐dioxane at 60°C to facilitate the ion‐exchange reaction.…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to the decomposition of ETFE and/or the grafted chains due to the high basicity of tetramethylammonium hydroxide. On the other hand, low basicity poly(1‐vinyl‐3‐propylimidazolium hydroxide)‐grafted ETFE (Im‐AEM/OH) was prepared to prevent the decomposition of ETFE in 1 M KOH at 80°C (Figure ) . However, an Im‐AEM/OH with an IEC = 0.85 mmol/g did not show conductivity after 150 h in 1 M KOH at 80°C because of ring‐opening hydrolysis of the imidazolium groups and β‐elimination of the imidazolium groups from the graft chains.…”
Section: Introductionmentioning
confidence: 99%
“…This result confirms the presence of N,Ndimethylethanolamine in the degradation products. Yoshimura et al [172] prepared a series of imidazolium-type AEMs through radiation grafting ways and used 13 C NMR to investigate the grafting result. NMR technology has also been used to investigate alkaline membranes prepared by chemical modification.…”
Section: Characterization Using Xps and Nmrmentioning
confidence: 99%
“…In a previous study, we reported the synthesis and characterization of a series of newly developed imidazolium cation based anion exchange membranes (AEMs) made by radiation-induced grafting of 1-vinylimidazole and styrene into poly(ethylene-cotetrafluoroethylene) (ETFE) films, and followed by N-alkylation with methyliodide. 1 These AEMs were characterized to be terpolymers, and showed better alkaline durability in 1 M KOH at 80 1C. Most lately, we have further modified the grafted imidazole group to 2-methyl-1-vinylimidazole, and the resultant AEMs (hereafter named 2Me-AEM) exhibit even higher ion conductivity (4100 mS cm À1 ) and longer alkaline durability, owing to the fact that the methyl protecting group at the 2-imidazole position prevents ring-opening degradation.…”
Section: Introductionmentioning
confidence: 99%